2009
DOI: 10.1074/jbc.m804413200
|View full text |Cite
|
Sign up to set email alerts
|

Regions of Melanocortin 2 (MC2) Receptor Accessory Protein Necessary for Dual Topology and MC2 Receptor Trafficking and Signaling

Abstract: MRAP, melanocortin 2 (MC2) receptor accessory protein, is required for trafficking by the MC2 (ACTH) receptor. MRAP is a single transmembrane protein that forms highly unusual antiparallel homodimers. We used molecular complementation to ask where MRAP achieves dual topology. Fragments of yellow fluorescent protein (YFP) were fused to the NH 2 or COOH terminus of MRAP such that YFP fluorescence could occur only in antiparallel homodimers; fluorescence was present in the endoplasmic reticulum. MRAP retained dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
154
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 28 publications
3
154
0
2
Order By: Relevance
“…In the absence of MC2R accessory protein (MRAP), MC2R is known to be retained in the endoplasmatic reticulum (ER) where it is degraded. However, in the presence of MRAP, MC2R is glycosylated and translocated to the plasma membrane where it is capable ACTH binding (Sebag & Hinkle 2009). Novel research has suggested that all MCRs may employ an accessory protein.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of MC2R accessory protein (MRAP), MC2R is known to be retained in the endoplasmatic reticulum (ER) where it is degraded. However, in the presence of MRAP, MC2R is glycosylated and translocated to the plasma membrane where it is capable ACTH binding (Sebag & Hinkle 2009). Novel research has suggested that all MCRs may employ an accessory protein.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of mouse MRAP and MRAP2 plasmids has been described before (4). ER-tracker blue-white DPX was purchased from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The MC2 receptor is also unusual in its requirement for an accessory protein, the MC2 receptor accessory protein (MRAP) (2). MRAP must be expressed with the MC2 receptor in order for the receptor to undergo glycosylation, traffic to the plasma membrane, bind ACTH, and stimulate adenylyl cyclase (2)(3)(4). Individuals with inactivating mutations of either the MC2 receptor or MRAP suffer from ACTH resistance and severe glucocorticoid deficiency (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al (2009) demonstrated that both MRAP1 and MRAP2 enhance MC2R but inhibit MC1R, MC3R, MC4R and MC5R signalling ability. By contrast, Sebag & Hinkle (2009b) showed defects on MC2R signalling when co-expressed with MRAP2 despite its correct trafficking to the cell membrane. These contradictory results may be explained considering the ACTH concentration used in the assays, as only supraphysiological doses of ACTH used by Chan et al (2009) were capable of inducing an activation of MC2R in the presence of MRAP2 (Sebag & Hinkle 2009b).…”
Section: Melanocortin System: Receptors Ligands and Accessory Proteinsmentioning
confidence: 88%